2017
DOI: 10.1186/s40529-017-0178-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification among morphologically similar Argyreia (Convolvulaceae) based on leaf anatomy and phenetic analyses

Abstract: BackgroundThe genus Argyreia Lour. is one of the species-rich Asian genera in the family Convolvulaceae. Several species complexes were recognized in which taxon delimitation was imprecise, especially when examining herbarium materials without fully developed open flowers. The main goal of this study is to investigate and describe leaf anatomy for some morphologically similar Argyreia using epidermal peeling, leaf and petiole transverse sections, and scanning electron microscopy. Phenetic analyses including cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Three of these spirit specimens were examined with a scanning electron microscope (Hitachi SU8010) [38,109] to study the surface of the floral nectary. The other three spirit specimens were examined via anatomical techniques using the paraffin method [89,[110][111][112]. Briefly, the paraffin method requires all water to be removed from the spirit specimens by first using a vacuum and then dehydrating the tissue with tert-Butyl alcohol (TBA) series [89,[110][111][112].…”
Section: Floral Nectary Anatomy and Micromorphologymentioning
confidence: 99%
“…Three of these spirit specimens were examined with a scanning electron microscope (Hitachi SU8010) [38,109] to study the surface of the floral nectary. The other three spirit specimens were examined via anatomical techniques using the paraffin method [89,[110][111][112]. Briefly, the paraffin method requires all water to be removed from the spirit specimens by first using a vacuum and then dehydrating the tissue with tert-Butyl alcohol (TBA) series [89,[110][111][112].…”
Section: Floral Nectary Anatomy and Micromorphologymentioning
confidence: 99%
“…Figure 3a shows the presence of guard cells and neighbouring cells at a magnification of 12.5x10. According to (Mulyani, 2006) explains that in stomata, two special cells limit the stomata, called guard cells, and some (Traiperm et al, 2017). This is in line with (Resmi, 2019) in a journal entitled Stomatal Types In Monocot And Dicot Plants Within Flora Of Nirmala College Campus explained that research on 40 plants collected, 16 plants showed anomocytic stoma, one of which was from the Apocynaceae family, Tabernaemontana sp.…”
Section: Discussionmentioning
confidence: 66%
“…In Convolvulaceae, these characters have also been consistent and informative, such as the type of mesophyll that was used to delimit three species of Evolvulus (Ketjarun et al 2016), the shape of the main vein and vascular bundles used to clarify the relationship between morphologically similar Argyrea species (Traiperm et al 2017). Furthermore, anatomical characters strongly supported species identification in an investigation of Merremia section Xanthips (Pisuttimarn et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…These characters are considered consistent (Metcalfe and Chalk 1979) and useful for Convolvulaceae taxonomy (e.g. Ketjarun et al 2016;Traiperm et al 2017). Ipomoea maranhensis can also be compared to I. langsdorffii Choisy, an endemic species from the Southeastern region of Brazil occuring in the Cerrado and Atlantic forest, due to its oblong leaves and flowers in dichasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation